De grenzen voorbij : een wereldwijde catastrofe of een duurzame wereld - Meadows, Donella H.; Meadows, Dennis L.; Randers, Jorgen (Utrecht: Spectrum, 1992)
"Donella H. Meadows, Dennis L. Meadows, Jorgen Randers"